Socialization of Efforts to Increase Environmental Awareness in Pangambatan Village as A Tourist Attraction in Karo Regency - Tampubolon, Flansius; Sinulingga, Jekmen (Talenta Publisher, 2021)
This service aims to provide environmental care socialization in Pangambat village. As a tourist village, Pangambaten village has problems in dealing with environmental challenges related to environmental cleanliness, so there is a need to educate and inform the community about environmental problems. One of the commitments of the international community and government in protecting the earth from pollution and damage is through the implementation of Environmental Education, which is the key to preparing people with knowledge, expertise, values ​​and a caring attitude so that they can actively participate in solving environmental problems. The counseling on environmental care in this service program is intended as an initial step in building a character that cares about the environment in the community. This service was carried out in Pangambaten, Tanah Karo Regency, North Sumatra Province. This service is carried out in two methods, namely the interactive presentation method. This service activity is carried out in the following stages: 1) Equalization of Community Group Perceptions, 2) Group coaching, 3) Counseling on understanding about fostering environmental concern for environmental cleanliness by reviving the tradition of mutual cooperation.